Solitary fibrous tumor of the bladder: A rare cause of bladder outlet obstruction in an adult male - Návan vanJaarsveld; Alessandro Pietro Aldera; Jeff John (IJU Case Reports)
Introduction Solitary fibrous bladder tumors are extremely uncommon, with only a few cases reported. These fibroblastic mesenchymal neoplasms are typically benign, indolent, and slow growing. Case presentation A 44‐year‐old male patient with obstructive uropathy was referred to our unit for workup. Ultrasonography and MRI of the pelvis showed a large, well‐circumscribed bladder mass, also visualized cystoscopically. This mass was excised en bloc using the Pfannenstiel approach. Histopathological and immunohistochemical analyses revealed a solitary fibrous tumor. Conclusion The management of SFTs can be challenging due to the lack of established guidelines. Hence, we offered our patient long‐term follow‐up. Twelve months postoperatively, no recurrence or metastases were found on the follow‐up imaging.